Highly expressed GCN1 is associated with cancer progression and poor prognosis in hepatocellular carcinoma patients - Zhongchao Zhang; Caijun Rao; Mingcun Hu; Wei Yan; Zhipeng Du (Cancer Cell International)
Abstract Background General control non-derepressible protein 1 (GCN1), a ribosome-binding protein, has been implicated in the development and progression of multiple cancers. However, the potential role of GCN1 in hepatocellular carcinoma (HCC) has not yet been investigated. Methods The expression of GCN1 in HCC was analyzed using multiple databases. Bioinformatics analysis was employed to investigate the correlation of GCN1 expression with clinical significance and immune infiltration in HCC. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, gene set enrichment analysis (GSEA), and in vitro experiments were conducted to study the function and potential mechanisms of GCN1 in HCC. Results GCN1 was significantly upregulated in HCC, which was associated with worse clinicopathological features and poorer prognosis of the patients. GCN1 expression was closely associated with immune cell infiltration in HCC. GSEA analysis showed that GCN1 was involved in several tumor-related signaling pathways, including cell cycle, DNA replication, and Wnt signaling pathway. Knockdown of GCN1 inhibited the proliferation, invasion and migration of HCC cells, and also down-regulated the expression levels of cell cycle protein cyclin B1 (CCNB1), cyclin D1 (CCND1), and Wnt signaling pathway-related proteins Wnt3A and β-catenin. Conclusion GCN1 overexpression was associated with HCC progression and poor prognosis, and GCN1 knockdown could suppress the proliferation, migration and invasion ability of HCC cells by regulating Wnt signaling pathway, suggesting the potential of GCN1 as a prognostic and therapeutic target for HCC.